2017
DOI: 10.3126/jpan.v4i1.16742
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depression among elderly living in old age homes of Kathmandu Valley and its association with Sociodemographic variants

Abstract: Introduction: There has been a considerable increase in the numbers of older people in the world population of both developed and developing countries. The increasing elderly populations are prone to depression. Studies regarding depression among elderly, especially in old age homes is lesser in the developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…This evidence agreed with the evidence revealed from Brazil, Sri Lanka, and India [ 32 , 44 , 45 ] respectively. The possible explanations for the discrepancies between females and males being exposed to depression because of biological differences, that is females affected by pregnancy and related physiological changes [ 32 ]. And also females take the majority of household responsibilities, and they depend on men economically; particularly in poorer settings [ 44 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This evidence agreed with the evidence revealed from Brazil, Sri Lanka, and India [ 32 , 44 , 45 ] respectively. The possible explanations for the discrepancies between females and males being exposed to depression because of biological differences, that is females affected by pregnancy and related physiological changes [ 32 ]. And also females take the majority of household responsibilities, and they depend on men economically; particularly in poorer settings [ 44 ].…”
Section: Discussionsupporting
confidence: 91%
“…We had also assessed clinical conditions that might contribute to depression such as hypertension, diabetes mellitus, heart diseases, epilepsy, and HIV/AIDS. Geriatric depression scale item 15 has been extensively tested and validated in low and middle-income countries such as India, Nepal, and other Asian countries [ 15 , 31 , 32 ]. It has been also checked in Ethiopian regions by previous studies [ 6 , 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…The study also found that older adults suffered more number of chronic diseases, they were more at risk of depression. This result is supported by many studies which reported that there was high risk of depressive disorders among those with physical illness (Dao et al, 2018;Fiske et al, 2009;Hassanzadeh et al, 2017;Kafle et al, 2015;Peltzer and Phaswana-Mafuya, 2013;Pocklington, 2017). It is worth noting that the relationship between depression and chronic disease is particularly complex when they coexist.…”
Section: Prevalence Of Depressionmentioning
confidence: 62%
“…This is in line with few previous studies ( Buvneshkumar et al, 2018 ; Girma et al, 2016 ). A survey on ethnic minorities in Central Highland Vietnam reported that educational level of ethnic minority groups is low and the percentage of people drop further as the level of education rises and as a result, opportunities to get a job with professional and technical qualifications are limited ( Kafle et al, 2015 ; UNFPA, 2009 ). People with high levels of education are likely employed in well-paid jobs or appointed to more socially recognizable positions; however, they may be more at risk of having depression when they are retired because of reduction in income and decline in social interaction.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study carried out in Nepal has already proved that GDS was a reliable tool to screen depression in the Nepalese patients which showed Cronbach's Alpha= 0.79. 12 Ethical approval was taken from Shree Medical and Technical College Institutional Review Committee (Ref: SMTC-IRC-20201230-05). Permission was also taken from the concerned authorities of old-age homes of Devghat, Tanahun.…”
Section: Methodsmentioning
confidence: 99%